Fran göticism till ’det svenska folklynnet’. Om äldre traditioner i svensk identitetsforskning - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2007)
National identity, in the meaning of a need to define oneself as a member of a nation and to characterize one's nation, is not constant. It increases during crises and transformations in state and society, and decreases in periods of stabilisation. In the case of Sweden, the research on the natłonal character and identity flourished in the 19th and the early 20th century, which was crucial time politically, economically and socially. The main trends in a searching for the Swedish identity, which are discussed in this article, were inspired by the Nordic mjrthology, the so called great power period in the Swedish history (the 17th century) and the folk traditions symbolised by the province of Dalecarlia. This article presents also the attempts to portray the Swedish national character by C. L. J. Almqvist, V. von Heidenstam, E. Key, A. Strindberg and G. Sundbarg.